2000
DOI: 10.1007/s001150050658
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrische und somatische Morbidität bei Patienten mit vermuteter Multiple Chemical Sensitivity (MCS)

Abstract: Multiple chemical sensitivity (MCS) or idiopathic environmental intolerance (IEI) is understood as an acquired disorder with multiple recurrent symptoms that cannot be traced to any well-known medical or psychiatric condition and is associated with diverse environmental influences that are well tolerated by the majority of people. In a prospective study, we investigated 120 consecutive patients admitted a university-based outpatient department for environmental medicine during 1 year. Apart from routine medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
0
3
0
6
Order By: Relevance
“…Von den Beschwerdeträgern suchten deshalb 81% den Arzt auf. Der Begriff "multiple chemical sensitivity (MCS)" wurde erstmals Ende der 80er-Jahre durch Cullen (1987) als ein Komplex erworbener rezidivierender und heterogener Körperbeschwerden beschrieben, die durch eine Exposition gegenüber niedrigen, für Normalpersonen problemlos tolerierbare Konzentrationen von Schadstoffen aus der Umwelt ausgelöst werden und deren Symptomatik durch keine bekannte medizinische und/oder psychische Störung erklärbar ist (Bornschein et al 2000). Die Betroffenen selbst führen ihre vielfältigen kör-perlichen und psychischen Beschwerden, wie Herz-Kreislauf-, Magen-Darm-, Haut-Schleimhaut-Symptome, Angst, Depressivität, Ermüdung und Energieverlust, Kopfschmerzen, Schwindel und Benommenheit auf die Exposition chemischer Stoffe zurück.…”
Section: Schlüsselwörterunclassified
See 1 more Smart Citation
“…Von den Beschwerdeträgern suchten deshalb 81% den Arzt auf. Der Begriff "multiple chemical sensitivity (MCS)" wurde erstmals Ende der 80er-Jahre durch Cullen (1987) als ein Komplex erworbener rezidivierender und heterogener Körperbeschwerden beschrieben, die durch eine Exposition gegenüber niedrigen, für Normalpersonen problemlos tolerierbare Konzentrationen von Schadstoffen aus der Umwelt ausgelöst werden und deren Symptomatik durch keine bekannte medizinische und/oder psychische Störung erklärbar ist (Bornschein et al 2000). Die Betroffenen selbst führen ihre vielfältigen kör-perlichen und psychischen Beschwerden, wie Herz-Kreislauf-, Magen-Darm-, Haut-Schleimhaut-Symptome, Angst, Depressivität, Ermüdung und Energieverlust, Kopfschmerzen, Schwindel und Benommenheit auf die Exposition chemischer Stoffe zurück.…”
Section: Schlüsselwörterunclassified
“…Diese somatogenen Hypothesen konnten jedoch nicht empirisch hinreichend belegt werden (Simon et al 1993;Kieswetter et al 1999). Dagegen zeigten über viele Studien hinweg MCS-Patienten Zusammenhänge mit psychischen Störun-gen auf, insbesondere mit somatoformen, affektiven und Angststörungen (Bornschein et al 2000), wobei aufgrund der Querschnittsuntersuchungen nicht geklärt werden konnte, ob diese als Ursache oder als Folge der MCS einzuschätzen sind.…”
Section: Introductionunclassified
“…Several studies have reported associations between symptoms of IEI and emotional distress, such as increased levels of anxiety, somatization and depressive symptoms [6][7][8][9][10][11][12][13][14][15]. Evidence also points to an association between IEI and psychological traits thought to be involved in the maintenance of symptoms in functional somatic disorders [6,7,13,16,17], which taken together may suggest a role of affect regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic environmental intolerance has been defined as an acquired condition with multiple recurrent symptoms that are connected with exposure to diverse environmental chemicals well tolerated by most people and that cannot be explained by any known medical, psychiatric, or psychological disorder (1). There is a high comorbidity with psychiatric disorders such as depression, anxiety, and somatoform disorders (2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%